Les écoles de journalisme face à l’expansion du marché. Stratégies d’internationalisation et transformations des curricula - Samuel Bouron (Cahiers de la Recherche sur l'Education et les Savoirs)
Describing the evolution of curricula in journalism schools, this text describes the struggle led by different fractions of the professional elite to legitimize their training model. On the one hand, both landmark schools of journalism, ESJ Lille and CFJ, have built a model of professional excellence based on “general knowledge” and expect their graduates to engage into “serious” journalism. On the other hand, more recent schools, like the School of Journalism at Sciences-po and the IPJ, have drawn their inspiration from American universities and have included special subjects in their curriculum to be in keeping with the labor market’s demands. For these schools, the challenge is then to construct a curriculum that overcomes the contradictions between these models of professional excellence.